2023
DOI: 10.3389/fsufs.2023.1243722
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the contribution of formal and local seed systems to household seed security in eastern Zimbabwe

Bulisani L. Ncube,
Rachel Wynberg,
Shawn McGuire

Abstract: IntroductionInterventions aimed at improving the seed security of smallholder farmers do not always yield positive results. Governments, donors, and other actors have neglected local seed systems as they are assumed to be incapable of addressing farmers’ seed challenges. Instead, external actors use seed aid and formal seed provisioning outlets, such as agro-input dealers, to channel seed to farmers. This paper compares the “formal” seed systems, mainly comprising certified seed obtained from government and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…A study conducted in six African countries found that 90.2% of seed obtained by producers comes from informal systems [ 24 ]. Local seed systems play a crucial role in enhancing seed security for resource poor farmers and promoting crop diversification [ 76 ]. About 50% of Ugandan farmers used their own farm-saved seed [ 22 ], while 40% of Ethiopian farmers used wheat seed from the formal sector [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in six African countries found that 90.2% of seed obtained by producers comes from informal systems [ 24 ]. Local seed systems play a crucial role in enhancing seed security for resource poor farmers and promoting crop diversification [ 76 ]. About 50% of Ugandan farmers used their own farm-saved seed [ 22 ], while 40% of Ethiopian farmers used wheat seed from the formal sector [ 77 ].…”
Section: Discussionmentioning
confidence: 99%